Saving and attitude: an evidence from household saving in the jaffna district - Karunaanithy, K.; Santhirasegaram, S. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Saving located within economic psychology plays an important role in individual, household and country’s development. As saving decisions areinfluenced by attitudinal factors, this study attempts to identify them by applying a factor analysis because of the latentnature of saving. Based on stratified random sampling method 500 households were selected from 5 job groups from all DS divisions of the Jaffna district. Questionnaire with 21 Likert type questionswas used to collect data under a survey method. Six factors emerged out of the factor analysis and accounted for 52% of variance. ‘need for saving’ and ‘competency in finance’ ‘formal sector saving habit’,‘debt avoidance’ correlated positively and significantly with saving. Households which understand the need for saving, who are competent in financial matters, have a habit of formal sector saving, and wish to avoid debt have a positive attitude towards saving. Therefore, results of this study propose that policy measures which aim to enhance household saving should consider about these attitudinal factors when developing saving instruments. It might be beneficial to identify individual differences in attitude as it helps the proposed development framework for the Northern Province as saving is indispensable for accumulation of investment.
Keywords: Economic psychology; Attitude; Attitudinal Factors; Household Saving